(untitled) (Physical Education, Health and Social Sciences, 2025)
The human gastrointestinal microbiome is a highly intricate network of trillions of biological microorganisms that include complex microbial ecosystems that are useful to the human health status by governing digestion, immunity, metabolism, and neurological health. Microbial imbalance, also known as dysbiosis, has been associated with diverse pathologies, such as gastrointestinal diseases (e.g. IBD, IBS), metabolic disorders (e.g. obesity, diabetes) and neuropsychiatric disorders. Future microbiota-based interventions including probiotics, prebiotics, synbiotics, postbiotics, and fecal microbiota transplantation (FMT) provide hopeful avenues that solve this problem by restoring microbe-biotic balance and alleviating these disorders. FMT proved to be amazing in frequent infections of Clostridioides difficile, whereas probiotics and prebiotics have revealed promise in treating IBS and metabolic disorders. There are, however, some difficulties such as the absence of clear mechanisms of actions, strain-specific variability, and the necessity of personalized methods. As well, the functions of non-bacterial microbiota (e.g., fungi, viruses) are understudied. This article will summarize the recent literature, show the current achievements in treatment, and outline research gaps in light of necessity to conduct more clinical trials and interdisciplinary research to realize the full potential of microbiome-based medicine. Filling these gaps may transform the treatment approaches to the disease of the gut and bodywide diseases.